Vitamin B12 levels in thyroid disorders: A systematic review and meta-analysis - Benites-Zapata, Vicente A. (2023)
Background and aims: Numerous studies have found an association between vitamin deficiency and thyroid disorders (TD). The presence of anti-parietal cell antibodies is indicative of reduced ability to absorb vitamin B12. Thus, this study reviewed the existing studies with the objective of assessing differences in the serum levels of vitamin B12 among patients with and without TD, the frequency of vitamin B12 deficiency in patients with TD, and the presence of anti-parietal cell antibodies in patients with TD. Methods: A meta-analysis of random-effects model was conducted to calculate pooled frequencies, mean differences (MD), and their respective 95% confidence intervals (CI). We identified 64 studies that met our inclusion criteria (n = 28597). Results: We found that patients with hypothyroidism had lower vitamin B12 levels than healthy participants (MD: −60.67 pg/mL; 95% CI: −107.31 to −14.03 pg/mL; p = 0.01). No significant differences in vitamin B12 levels were observed between healthy participants and patients with hyperthyroidism (p = 0.78), autoimmune thyroid disease (AITD) (p = 0.22), or subclinical hypothyroidism (SH) (p = 0.79). The frequencies of vitamin B12 deficiency among patients with hypothyroidism, hyperthyroidism, SH, and AITD were 27%, 6%, 27%, and 18%, respectively. Conclusions: Patients with hypothyroidism had lower levels of vitamin B12 than healthy participants. No significant differences were observed between vitamin B12 levels and hyperthyroidism, AITD, or SH. Systematic Review Registration: https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=324422, identifier (CRD42022324422). Copyright © 2023 Benites-Zapata, Ignacio-Cconchoy, Ulloque-Badaracco, Hernandez-Bustamante, Alarcón-Braga, Al-kassab-Córdova and Herrera-Añazco.